Pengaruh Lingkungan Kerja Fisik Dan Motivasi Terhadap Kinerja Karyawan Pada PT Pos Indonesia (Persero) Cabang Ciputat Kota Tangerang Selatan - Ayu Fitria; Shela Indah Savitri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of the physical work environment and motivation on employee performance at PT Pos Indonesia (Persero) Ciputat Branch, South Tangerang City. The research employs a quantitative method with a survey approach. Data were collected through questionnaires using the Slovin formula, resulting in 62 respondents representing a population of 160 employees. Data analysis techniques include validity and reliability tests, classical assumption tests, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing.The results indicate that the physical work environment has a significant effect on employee performance, as evidenced by the hypothesis test where t-count > t-table (9.318 > 1.671). Motivation also significantly affects employee performance with t-count > t-table (9.101 > 1.671). Simultaneously, the physical work environment and motivation influence employee performance with F-count > F-table (60.672 > 4,004). The coefficient of determination is 67.3%, meaning that employee performance is influenced by the physical work environment and motivation by 67.3%, while the remaining 32.7% is influenced by other variables not examined in this study.